2013
DOI: 10.1159/000347228
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Safety Study of First-Line Bevacizumab in Combination with Standard Chemotherapy in Chinese Patients with Metastatic Colorectal Cancer Treated in an Expanded Access Program in Taiwan

Abstract: Objective: An increased risk of serious adverse effects related to bevacizumab has been observed in many Western studies for metastatic colorectal cancer. To evaluate the safety of bevacizumab in Chinese patients, a safety study was conducted in Taiwan. Methods: Bevacizumab was provided by the Expanded Access Program in combination with first-line chemotherapy per investigator's choice. The primary objective is the safety profile, particularly the targeted adverse events such as proteinuria, bowel perforation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a report from Taiwan where bevacizumab is reimbursed by the government for the first-line treatment of metastatic CRC when combined with irinotecan-based chemotherapy, the efficacy and toxicity of bevacizumab-based chemotherapy seemed to be comparable with the Western studies. 108 …”
Section: Treatment Options For Metastatic Diseasementioning
confidence: 99%
“…In a report from Taiwan where bevacizumab is reimbursed by the government for the first-line treatment of metastatic CRC when combined with irinotecan-based chemotherapy, the efficacy and toxicity of bevacizumab-based chemotherapy seemed to be comparable with the Western studies. 108 …”
Section: Treatment Options For Metastatic Diseasementioning
confidence: 99%
“…Fifteen included studies encompassing 5891 patients reported on the prevalence of VTE in colorectal cancer patients undergoing chemotherapy [ 34 , 42 , 44 , 53 , 55 , 59 , 88 , 102 , 106 , 110 , 111 , 118 , 122 , 125 , 126 ]. The meta-analysis revealed a pooled estimated prevalence of 5%, ranging from 3 to 7% (ES 5%; 95% CI 3–7%; z = 8.16; p < 0.001) ( Table 4 and Supplemental SI Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%